PRKCQ promotes oncogenic growth and anoikis resistance of a subset of triple-negative breast cancer cells. Issue 1 (December 2016) - Byerly, Jessica; Halstead-Nussloch, Gwyneth; Ito, Koichi; Katsyv, Igor; Irie, Hanna
Abstract Background The protein kinase C (PKC) family comprises distinct classes of proteins, many of which are implicated in diverse cellular functions. Protein tyrosine kinase C theta isoform (PRKCQ)/PKCθ, a member of the novel PKC family, may have a distinct isoform-specific role in breast cancer. PKCθ is preferentially expressed in triple-negative breast cancer (TNBC) compared to other breast tumor subtypes. We hypothesized that PRKCQ/PKCθ critically regulates growth and survival of a subset of TNBC cells. Methods To elucidate the role of PRKCQ/PKCθ in regulating growth and anoikis resistance, we used both gain and loss of function to modulate expression of PRKCQ. We enhanced expression of PKCθ (kinase-active or inactive) in non-transformed breast epithelial cells (MCF-10A) and assessed effects on epidermal growth factor (EGF)-independent growth, anoikis, and migration. We downregulated expression of PKCθ in TNBC cells, and determined effects on in vitro and in vivo growth and survival. TNBC cells were also treated with a small molecule inhibitor to assess requirement for PKCθ kinase activity in the growth of TNBC cells. Results PRKCQ/PKCθ can promote oncogenic phenotypes when expressed in non-transformed MCF-10A mammary epithelial cells; PRKCQ/PKCθ enhances anchorage-independent survival, growth-factor-independent proliferation, and migration. PKCθ expression promotes retinoblastoma (Rb) phosphorylation and cell-cycle progression under growth factor-deprived conditions that typically induce cell-cycle arrest of MCF-10A breast epithelial cells. Proliferation and Rb phosphorylation are dependent on PKCθ-stimulated extracellular signal-related kinase (Erk)/mitogen-activated protein kinase (MAPK) activity. Enhanced Erk/MAPK activity is dependent on the kinase activity of PKCθ, as overexpression of kinase-inactive PKCθ does not stimulate Erk/MAPK or Rb phosphorylation or promote growth-factor-independent proliferation. Downregulation of PRKCQ/PKCθ in TNBC cells enhances anoikis, inhibits growth in 3-D MatrigelTM cultures, and impairs triple-negative tumor xenograft growth. AEB071, an inhibitor of PKCθ kinase activity, also inhibits growth and invasive branching of TNBC cells in 3-D cultures, further supporting a role for PKCθ kinase activity in triple-negative cancer cell growth. Conclusions Enhanced PRKCQ/PKCθ expression can promote growth-factor-independent growth, anoikis resistance, and migration. PRKCQ critically regulates growth and survival of a subset of TNBC. Inhibition of PKCθ kinase activity may be an attractive therapeutic approach for TNBC, a subtype in need of improved targeted therapies.